Graph matching approach and generalized median graph for automatic labeling of cortical sulci with parallel and distributed algorithms - Felouat, Hichem; Oukid-Khouas, Saliha (Cognitive systems research, 2019)
The human brain cortex is very complex structure containing folds (gyri) and fissures (sulci) that were the subject of our study in this paper. The sulcus is one of the most important features in order to know the different functions areas of the brain. The exact identification of sulci on human brain using MRI images is helpful in many studies and applications related to brain diseases and human behavior. Automatic labeling of cortical sulci with all this complexity and inter-subject variability, this is considered non-trivial task. In this paper, we have proposed a new graph based approach of automatic labeling of cortical sulci with parallel and distributed algorithms using graph matching and generalized median graph. The graph matching is very important in many studies and applications such as pattern recognition and classification. The generalized median graph of a set of graphs is a way to represent a set of graphs by a comprehensive graph that minimizes the sum of the distances to all graphs. We have used the characteristics of shape, orientation and location to describe the sulci. The results that we have obtained prove that our approach is accurate and acceptable in this field which uses the graph matching for automatic labeling of cortical sulci.